Therapeutic Management of Incontinence and Pelvic Pain Pelvic Organ Disorders - Haslam, J.; Haslam, J.; Laycock, J.; Laycock, J. (Springer London : Imprint: Springer, 2007)
Therapeutic Management of Incontinence and Pelvic Pain, 2nd edition contains contributions from many of the well-known authors of the successful first edition, who have updated their chapters in light of more recent research. Chapters include coverage of the management and treatment of bladder and bowel dysfunctions in men and women, pelvic organ prolapse; issues concerning the elderly, neurologically impaired patients and those with pelvic pain. Allied updated chapters are presented on research methodology, the importance of fluids and infection control. Other new chapters are concerned with quality of life, the treatment of bladder and bowel dysfunction in children, the history of pelvic floor muscle exercise and manual therapy. In addition, the use of real-time ultrasound to evaluate pelvic floor muscle contractility, exercise balls to promote coordination of trunk stabilisers and the pelvic floor muscles, and the role of the Occupational Therapist in the continence service are discussed. Finally, a new section on ethical issues regarding the management of incontinence completes this well-illustrated text. This book will be of interest to physiotherapists and nurses working in the continence field, and to all health professionals who wish to gain a better insight into the conservative management of pelvic floor muscle disorders. It will enable the reader to question their present practice and will help in encouraging further research.